Crude Oil Demulsification Using Electro-Coalescence Method: A Comprehensive Review - Shallal, Ahmed; Al-zobai, Khalid M. Mousa; Al-Dawery, Salam K. (Al-Nahrain Journal for Engineering Sciences, 2025)
The separation of water from crude oil emulsions is a critical and complex challenge in petroleum production and processing. Water-in-oil (W/O) emulsions increase viscosity, pose corrosion risks, reduce refining efficiency, and raise significant environmental concerns. Traditional separation methods often struggle with stable emulsions containing small droplets due to limitations in cost, environmental impact, and effectiveness. Electro-coalescence demulsification has emerged as a promising technique that applies electric fields to enhance droplet coalescence, facilitating efficient water removal. This comprehensive review examines the influence of electrode geometry on electro-coalescence systems in depth, synthesizes key findings from numerous studies, and provides a detailed analysis of electrode spacing calculations, critical conditions for effective demulsification, and optimal operational parameters. By exploring these aspects comprehensively, the review offers insights into how electrode design affects demulsification efficiency, guiding future advancements in crude oil processing and contributing to more sustainable practices in the petroleum industry.